Malicious Objects, Anger Management, and the Question of Modern Literature - Kreienbrock, Jorg (Book collections on Project MUSE., 2012)
By investigating the minutest details of life among dysfunctional household items through the discourses of philosophy and science, as well as in literary works by Laurence Sterne, Jean Paul, Friedrich Theodor Vischer, and Heimito von Doderer, Kreienbrock reconsiders the modern bourgeois poetics that render things the way we know and suffer them.